Mucin 1-specific B cell immune responses and their impact on overall survival in breast cancer patients. (2nd January 2016) - Fremd, Carlo; Stefanovic, Stefan; Beckhove, Philipp; Pritsch, Maria; Lim, Hendry; Wallwiener, Markus; Heil, Joerg; Golatta, Michael; Rom, Joachim; Sohn, Christof; Schneeweiss, Andreas; Schuetz, Florian; et al.
Abstract : Considering the diverse functions of B cells, responses to tumor-associated antigens (TAA) have been thought to be the main source of B cell-mediated antitumor immunity. Polymorphic epithelial mucin (MUC1) is considered one of the most specific TAA in patients with breast cancer. The present study aims to dissect the level and subclasses of naturally occurring anti-MUC1 antibodies in regard to tumor biologic parameters, clinical characteristics and overall survival. In 288 primary, non-metastatic breast cancer patients, pretreatment serum levels of anti-MUC1 immunoglobulin G (IgG) and its subclasses G1–4 as well as immunoglobulin M (IgM) were analyzed via ELISA. With respect to overall survival (Kaplan–Meier analysis), tumor biologic parameters as hormone receptor status, human epidermal growth factor receptor 2 (Her2), Ki-67 expression and tumor grading have been correlated as well as clinical characteristics as nodal involvement, tumor stage and patients' age at the time of diagnosis. Median follow-up time was 148 mo (IQR: 73.1–158.5 mo). A significant increase in IgG antibody titers was correlated highly significantly with an improved overall survival of patients. In multivariate analysis, total IgG proved to be an independent prognostic marker for overall survival ( p = 0.002). IgG subclass analysis did not reveal any correlation of IgG1, IgG3 and IgG4 levels with overall survival, while increased immunoglobulin G2 (IgG2) values, although statistically not significant, tended to correlate with prolonged patient survival. MUC1-specific IgM antibodies were shown not to be predictive of overall survival. Altogether, humoral immune responses appear to play a crucial part in the tumor immunity of breast cancer patients. The present data confirms the positive impact of tumor-specific IgG on prolonged overall survival in breast cancer patients. MUC1-antibody testing might be a useful tool to identify high-risk patients who may need adjuvant therapy and potentially might benefit from MUC1-directed immunotherapy.